MEDICINAL PLANTS AS ALTERNATIVE TREATMENTS FOR ORAL HEALTH PROBLEMS - Khan, Ishfaq; Khan, Azhar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Oral flora plays an important role in the day-to-day life for human beings and also they are important part of human digestive system. Simultaneously, besides their beneficial activities, they can be harmful to the human, and this can be evaluated as normal oral flora as opportunistic pathogens. To elevate oral sanitation, medicinal plant-based mouthwash can be used as mediator and acts as a part of efficient home care medication. In dentistry, the importance of plants has been acknowledged to cure diseases generated by several oral pathogens. Chemical drugs possess many side effects and act as a key factor responsible for developing drug-resistant microorganisms. Herbal mouthwash products have fewer side effects than chemical drugs. The worldwide requirement for substitutive prevention, treatment choices, and products for oral infections that are harmless, efficient, and low cost comes from the boost in infection occurrence. For maintaining oral sanitation, ample research has been attempted to calculate the effect of plants. The review has established to aggregate the data on herbs and plants which possess great response to the pathogens concerned with oral infections. The review will assist the researchers to discover and choose the plant to develop adequate medicine for establishing cost-effective treatment for oral hygiene.